ASHRAE Handbook 2020 : HVAC Sytems and Equipment - ASHRAE (Atlanta : ASHRAE, 2020)
The 2020 ASHRAE Handbook—HVAC Systems and Equipment discusses various systems and the equipment (components or assemblies) they comprise, and describes features and differences. This information helps system designers and operators to select and use equipment that is the best fit for a particular application or scenario. Subject matter experts on ASHRAE Technical Committees in each subject area have reviewed all chapters and revised them as needed for current technology and practice.
Keywords: Airco; Ventilatie